VARIASI KONSENTRASI DAN pH TERHADAP KEMAMPUAN KITOSAN DALAM MENGADSORPSI METILEN BIRU - Tammi, Turmuzi; Suaniti, Ni Made; Manurung, Manuntun (Jurnal Kimia (Journal of Chemistry); Vol. 7, No. 1 Januari 2013, 2013)
The effects of chitosan concentration and pH on adsorption properties of the chitosan extracted from shrimp shell waste to adsorb methylen blue had been studied. Chitosan was made by two steps namely the isolation of chitin and the chitin deacetylation. The chitin isolation itself was conducted by three sequence procedures which were deproteination, demineralization, and depigmentation. The deacetylation was conducted by heating the chitin obtained in the concentrated solution of NaOH 50% (w/v) at 90 o C for 120 minutes. The degree of the deacetylation was 54,65%. The maximum concentration of 0,2% (w/v) at pH 7 showed the highest adsorption (%D) of 50 mL  10 ppm methylene blue of 95,044%.
Keywords: shrimp shell waste, chitin, chitosan, potential adsorpstion (%D), methylene blue